Comparison of early postoperative outcome of laparoscopic and open inguinal hernia mesh repair - Garg, Pulkit; Pai, Sreekar Agumbe; Vijaykumar, Hosamath (International Surgery Journal, 2018)
Background: Laparoscopic hernia has all the benefits of a tension free repair. The aim of this study was to compare the early postoperative outcome of laparoscopic and open inguinal hernia mesh repair. Methods: This is a prospective study conducted at Ramaiah hospital Bangalore from June 2016 to July 2017. 70 cases of inguinal were included in the study hernia diagnosed clinically and radiologically who fulfilled the inclusion & the exclusion criteria. The principal operative techniques were laparoscopic hernioplasty (LH) and open inguinal mesh hernioplasty (OH). Results: 35 patients each were allotted to two group (LH and OH). The mean age was 50.53. LH group had significantly less postoperative pain than the OH group on 12, 24 and 72 hrs (P <0.05). Although the vas pain scores of LH group were also comparatively lower on postoperative day 14, these differences were not statistically significant. Than mean operative time was significantly higher for LH group (131.86 vs 80.29 min) although in bilateral cases the difference was considerably less but was still significant (138 vs 107 min). The mean hospital stay after surgery was less for LH group (2.68 vs 3.25 days) but was not statistically significant. (p = 0.073). Chronic pain persisted for 2 patients (5.7%) in OH group whereas none had chronic pain in LH group. Conclusions: Laparoscopic hernioplasty is equivalent to open repair in the treatment of inguinal hernia, with less post-operative pain, lower risk of wound infection, shorter duration of hospital stay, and less incidence of chronic pain however requires a long learning curve and is more expensive.